Sustainable Digital Economy Through Good Governance: Mediating Roles of Social Reforms and Economic Policies - Xianbin, Tang; Qiong, Wu (Frontiers in Psychology, 2021)
The most powerful and crucial concept today is that of a sustainable digital economy. This research aims to investigate the predictors of a sustainable digital economy in China. In addition, the mediating roles of social reforms and economic policies were investigated between good governance and a sustainable digital economy. This cross-sectional research considered Partial Least Square – Structural Equational Modeling (PLS-SEM) as an analysis technique. The data was collected from 317 managerial staff of the e-commerce industry in China via a self-structured questionnaire. A random sampling technique was applied in the data collection process. Results showed that good governance has a positive impact on the sustainable digital economy, social reforms, and economic policies. Additionally, an increase in social reforms and economic policies led to a sustainable digital economy in China. Social reforms and economic policies were found to partially mediate the relationship between good governance and a sustainable digital economy. This research contributes to the body of knowledge by identifying components of a sustainable digital economy and examining whether good governance may aid in the attainment of a sustainable digital economy. Nowadays, research on the sustainable digital economy has got attention from policymakers and researchers around the globe. These outcomes suggest several ways to improve the sustainable digital economy in China. This research is not without limitations such as cross-sectional and based on respondent's responses. Several research avenues were discussed and can be influenced on many factors for future perspectives.